FALKE: Experiences From Transdisciplinary Educational Research by Fourteen Disciplines - Schilcher, Anita; Krauss, Stefan; Kirchhoff, Petra; Lindl, Alfred; Hilbert, Sven; Asen-Molz, Katharina; Ehras, Christina; Elmer, Michael; Frei, Mario; Gaier, Lisa; Gastl-Pischetsrieder, Maria; Gunga, Eileen; et al. (Frontiers in Education, 2021)
This article details how the FALKE research project (Fachspezifische Lehrerkompetenz im Erklären; Engl.: subject-specific teacher competency in explaining) integrates fourteen heterogeneous disciplines in order to empirically examine the didactic quality of teacher explanations in eleven school subjects by bringing together trans-, multi-, and interdisciplinary perspectives. In order to illustrate the academic landscape of the FALKE project we briefly outline the nature of the transdisciplinary German “Fachdidaktiken” (Engl.: subject-matter didactics, i.e., special academic disciplines of teaching and learning specific school subjects). The FALKE project required the willingness of all researchers from eleven participating subject-matter didactics to rely on both the concepts and the methods of educational sciences as an overarching research framework (transdisciplinary aspect). All researchers of subject-matter didactics had to develop a shared conceptual, methodological, and administrative framework in order to empirically investigate commonalities in and differences between “good explanations” across the range of school subjects represented (multidisciplinary aspect). The additional perspectives of researchers in speech science and linguistics proved fruitful in recognizing rhetorical and linguistic aspects of teacher explanations (interdisciplinary aspect). Data management and evaluation were provided by the discipline methods of educational sciences. Rather than reporting empirical results, we here discuss opportunities and challenges as well as the lessons learned from the FALKE project regarding cognitive-epistemic reasoning, communication, and organization.